PHYTOCHEMICAL STUDY ON THE ETHYLACETATE EXTRACT OF THE LEAVES OF Mesua ferrea LINN - S. M. Mizanur Rahman; Swati Shabnom; M. Abdul Quader; M. Amzad Hossain (Indonesian Journal of Chemistry, 2008)
Furano-napthyl-hydroxy cyclohexyl type of compound was isolated first times in plant from the ethyl extracts of the leaves of Mesua ferrea. The structure of the compound has been established by the modern spectroscopic techniques such as UV, IR, 1H-NMR, 13C-NMR and mass spectroscopy and identified as 12, 13-furano-8-hydroxy napthyl-6-0-b-2',3',4',6' tetrahydroxy-5',5' dimethyl cyclohexyl ether.